2020
DOI: 10.1038/s41598-020-77801-9
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of contrast enhanced ultrasound (CEUS) of hepatocellular carcinoma in patients with cirrhosis and transjugular intrahepatic portosystemic shunt (TIPS)

Abstract: Transjugular intrahepatic portosystemic shunt (TIPS) can treat portal hypertensive complications and modifies hepatic hemodynamics. Modification of liver perfusion can alter contrast enhancement dynamics of liver nodules. This study investigated the diagnostic performance of contrast-enhanced ultrasound (CEUS) to diagnose hepatocellular carcinoma (HCC) in cirrhosis with TIPS. In this prospective monocentric observational study, CEUS was used to characterize focal liver lesions in patients at risk for HCC with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It was assumed that the outflow of the vein could be neglected when contrast agents passed for the first time, and then, tissue perfusion was obtained according to the time-density curve of the artery and tissue organ. Besides, no contrast agent exosmosis occurred [ 19 ]. The concept of nondeconvolution model was simple and comprehensible, but it often underestimated BF.…”
Section: Discussionmentioning
confidence: 99%
“…It was assumed that the outflow of the vein could be neglected when contrast agents passed for the first time, and then, tissue perfusion was obtained according to the time-density curve of the artery and tissue organ. Besides, no contrast agent exosmosis occurred [ 19 ]. The concept of nondeconvolution model was simple and comprehensible, but it often underestimated BF.…”
Section: Discussionmentioning
confidence: 99%
“…At present, in addition to histopathological examination which is the only gold standard for the diagnosis of liver cancer, imaging examination has become one of the important standards. Conventional ultrasound or CT examination is the first choice for the diagnosis of liver cancer, but its specificity and sensitivity are low [ 3 ]. With the development of imaging technology, the application of contract enhanced ultrasound (CEUS) and enhanced CT/MRI in the qualitative diagnosis of liver cancer is becoming more and more mature [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analogously, the presence of a transjugular intrahepatic portosystemic stent shunt (TIPSS) can affect the contrast enhancement pattern in HCC. A very recent monocentric study by Chang et al reported APHE to occur earlier in HCC in the presence of a TIPSS, whereas contrast washout tended to occur more often and with a later onset in patients with a TIPSS [20]. However, of our sample size (two patients in the subgroup of typical HCC and six patients in the subgroup of atypical HCC) was too small for definite conclusions.…”
Section: Perfusion Alterationsmentioning
confidence: 60%